Clinical progress in genome-editing technology and in vivo delivery techniques. Issue 3 (March 2023) - Khirallah, Jennifer; Eimbinder, Maximilan; Li, Yamin; Xu, Qiaobing
Highlights: Genome editing has great potential for in vivo applications but challenges remain. There are many modes for the delivery of genome-editing tools, including viral vectors, lipid nanoparticles, polymers, and inorganic nanoparticles. There is a large gap between the number of genome-editing therapies in academia compared with those in clinical trials. Viral vectors are currently the gold standard, predominantly used in vivo, although lipid nanoparticles could be used to improve them further. Abstract: There is wide interest in applying genome-editing tools to prevent, treat, and cure a variety of diseases. Since the discovery of the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein (Cas) systems, these techniques have been used in combination with different delivery systems to create highly efficacious treatment options. Each delivery system has its own advantages and disadvantages and is being used for various applications. With the large number of gene-editing applications being studied but very few being brought into the clinic, we review current progress in the field, specifically where genome editing has been applied in vivo and in the clinic, and identify current challenges and areas of future growth.